A fabric coating material and preparation method thereof

Through block copolymer structure design and one-pot two-step synthesis technology, the problems of the existing medical protective clothing coating materials being unenvironmentally friendly, high cost and difficult to achieve the "three rejections" function are achieved, and efficient and environmentally friendly medical products are achieved Protective clothing coating material is prepared, with excellent bonding and "three-rejection" characteristics.

CN118854690BActive Publication Date: 2025-02-25HANGZHOU TRANSFAR FINE CHEM CO LTD +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411328477.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-25
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing medical protective clothing coating materials are not environmentally friendly and costly during the preparation process, and it is difficult to achieve the "three rejections" functions of water, oil and blood rejection at the same time.

Method used

Using block copolymer structure design, block copolymer is synthesized by a one-pot two-step process, including fluoroacrylate/long-chain alkylacrylate random copolymer segment A and bondable monomer/conventional acrylate monomer Random copolymer segment B uses microphase separation and surface enrichment characteristics of fluorine-containing segments to reduce the amount of fluorine-containing monomer and improve the "three-rejection" characteristics.

Benefits of technology

It achieves good bonding with the substrate, has excellent "three rejections" characteristics, reduces production costs, and is environmentally friendly in the process, avoiding the use of organic solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118854690B_ABST
    Figure CN118854690B_ABST
Patent Text Reader

Abstract

The present invention discloses a fabric coating material and a preparation method thereof. The coating material is a block copolymer composed of a fluoroacrylate / long-chain alkyl acrylate random copolymer segment A having "three-repellent" properties and an adhesive monomer / conventional acrylate random copolymer segment B. The block structure design can effectively improve the utilization efficiency of the "three-repellent" components, while having good fabric bonding performance, and effectively avoiding the antagonistic effect between polymer functions. The iodine transfer aqueous phase miniemulsion polymerization method is used to first synthesize the A segment, and then the chain is extended to synthesize the B segment. The prepared emulsion is applied to a substrate and dried to form a coating material. The process of the present invention can avoid the use of volatile organic solvents, the process is simple and environmentally friendly, and the obtained coating material has excellent water-repellent, oil-repellent and blood-repellent properties, and has broad application prospects in the fields of medical protective clothing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional additives for medical protective clothing, and particularly relates to a fabric coating material and a preparation method thereof. Background Art

[0002] Medical protective clothing is a consumable item that medical workers need to carry out patient diagnosis, treatment, nursing and other work. Since medical staff need to be exposed to a working environment with a certain viral load for a long time, high requirements are placed on the anti-pollution performance of medical protective clothing. At present, commercial medical protective clothing is mainly composed of fabrics made of polypropylene, polyethylene and polyethylene terephthalate as the main fabrics. This type of material has good hydrophobicity and barrier properties. However, when medical staff are exposed to the working environment, they will inevitably come into contact with liquids other than water, mainly including organic solvents such as alcohol, blood, etc. At the same time, after wearing protective clothing, it is easy to absorb dust in the air and has poor self-cleaning properties. The above fabrics that have not been surface treated are difficult to achieve water-repellent, oil-repellent, and blood-repellent effects at the same time. It is urgent to develop coating materials with strong adhesion to the fabric and can better achieve water-repellent, oil-repellent, and blood-repellent, that is, the "three-rejection" function.

[0003] The transparent hydrophobic and oleophobic coating disclosed in the patent "A transparent hydrophobic and oleophobic coating and its preparation method and the transparent hydrophobic and oleophobic coating formed" with publication number CN116694115A and the coating formed therefrom have good hydrophobic and oleophobic properties, UV aging resistance, light transmittance, hardness and self-cleaning properties, but the coating preparation method requires the use of modifiers, catalysts and organic solvents, and the reaction is relatively complicated and not environmentally friendly. The coating made of the super-hydrophobic and super-oleophobic modified liquid disclosed in the patent "A super-hydrophobic and super-oleophobic modified liquid and its preparation method, and a coating containing it" with publication number CN116355444A has super-hydrophobic, super-oleophobic, oil-resistant, wear-resistant and scouring-resistant properties, and still has super-hydrophobic and super-oleophobic functions after long-term aging outdoors, but it contains inorganic nanopowders, micro-nano fibers, solvents and alkalis, and the preparation process is complicated and the cost is high. The patent with publication number CN116622288A, "Nano coating with high wear resistance, high weather resistance, super hydrophobic and super oleophobic properties, and preparation method and construction method thereof", discloses a double coating system in which the base coating has excellent adhesion, can adhere well to most substrates, and can construct a uniform spherical micron structure. The top coating is a spherical nanostructure and can be cured at room temperature. After curing, the coating has excellent super hydrophobicity, super oleophobicity, wear resistance and high weather resistance. However, a mixed organic solvent is used in the preparation process, and inorganic nanomaterials are added, so the preparation, processing and use requirements of the coating materials are relatively high.

[0004] Fluorine-containing polymers have low surface energy and excellent water and oil repellency, and are an important component of the preparation of "three-repellent" coatings. Currently, commercialized fluorine-containing polymer coating materials (such as Japan Asahi Glass Waterproofing Agent E600 and AGC's AsahiGuard E-SERIES) can give a variety of fabrics good washing durability and waterproofness, especially for non-woven fabrics. Waterproof and alcohol-proof finishing has achieved good results without destroying the original air permeability and appearance of the fabric. However, the polymers that constitute the coating are all random structures, and fluorine-containing monomers and other monomers exist in the form of random sequence structures. In order to exert good water and oil repellency effects, the amount of fluorine-containing monomers is usually high.

[0005] Block copolymers refer to two or more polymers (either homopolymers or random copolymers) with different structures connected by covalent bonds in the form of long chains. While maintaining the characteristics of each block polymer, a unique condensed state (such as microphase separation) structure can be formed, giving the block copolymers unique properties. Applying block copolymers to the development of coating materials with "three-repellent" properties can make the main "three-repellent" fluorinated polymer segments and the bonding components concentratedly distributed. By utilizing the characteristics of fluorinated polymers that are easy to enrich on the surface, they can still exert their excellent "three-repellent" properties while reducing the amount of fluorinated monomers, and the block copolymers containing bonding components can achieve strong bonding with fabrics. There are also some literature reports on the preparation of lyophobic coatings containing block copolymers at home and abroad. For example, Chakrabarty et al. synthesized poly (2,2,3,3,4,4,4,4-heptafluorobutyl acrylate-b-butyl acrylate) by reversible addition-fragmentation chain transfer radical polymerization and tested its film-forming surface water contact angle of 112.5°. Li et al. synthesized poly (hexafluorobutyl methacrylate-b-glycidyl methacrylate) by atom transfer radical polymerization and used it for hydrophobic modification of cotton fabrics. Detrembleur et al. co-deposited amphoteric fluorinated block copolymer emulsion with silica particles to prepare a transparent and super-hydrophobic coating. The preparation of the above fluorinated block copolymers adopts reversible addition-fragmentation chain transfer radical polymerization and atom transfer radical polymerization. The structure of the chain transfer agent or catalyst is relatively complex and the production cost is high. The composite of fluorinated block copolymers with inorganic nanoparticles is complicated, and there are problems such as nanoparticle agglomeration affecting its hydrophobicity and oleophobicity.

[0006] In summary, although the structural design and synthesis technology of coating materials with "three-rejection" effects have been reported to a certain extent, most of the film-forming media are still high-VOC organic solvents. It is urgent to develop a water-based coating method that has good adhesion to the substrate and has "three-rejection" functions to solve the above problems. At present, most commercial "three-rejection" coatings are random copolymers. The random copolymerization of the "three-rejection" component and the bonding component will inevitably affect their respective properties and produce antagonistic effects. At the same time, although block copolymers have attracted attention as a new development of "three-rejection" coating materials, the block copolymerization method used has shortcomings such as the difficulty of synthesizing the regulator. Summary of the invention

[0007] The purpose of the present invention is to provide a coating material having good adhesion to a protective clothing substrate and excellent "three-repellent" properties and a preparation method thereof, so as to solve the problems of environmental pollution and high cost in the current preparation process of liquid-repellent coatings.

[0008] As the first aspect of the present invention, the present invention provides a fabric coating material, which is a block copolymer composed of at least a fluoroacrylate / long-chain alkyl acrylate random copolymer segment A and a bonding monomer / conventional acrylate monomer random copolymer segment B; in the material, a block copolymer containing different properties of a "three-rejection" component and a bonding component is synthesized by a one-pot two-step method, which effectively solves the antagonism problem between the "three-rejection" component and the bonding component containing a polar group. The specific scheme is: the mass ratio of segment A to segment B is 30:70~70:30; and the bonding component monomer of segment B is one of acrylic acid, hydroxyethyl acrylate, glycidyl acrylate, glycidyl methacrylate, acryloyl morpholine, methoxyethyl acrylate and N-(3,4-dihydroxyphenylethyl) methacrylamide monomers or a mixture thereof; the conventional acrylate monomer is one of methyl acrylate, ethyl acrylate, butyl acrylate monomers or a mixture thereof; the mass ratio of the bonding component monomer to the conventional acrylate monomer is 30:70~50:50.

[0009] The adhesive monomer in the random copolymer segment B also ensures that the coating has a suitable glass transition temperature (or film-forming temperature), hardness and flexibility, while also reducing the cost of the coating material.

[0010] In addition, the present invention adopts a block copolymer structure design, which can effectively regulate its structure due to the microphase separation caused by the thermodynamic incompatibility of the block copolymer compared to the random copolymer. Therefore, the block copolymer coating can more efficiently play the role of the functional component, so that the "three-rejection" component and the bonding component each perform their respective functions, reduce the amount of the more expensive fluorine-containing polymer with the "three-rejection" characteristics, and reduce costs, wherein the "three-rejection" characteristics are mainly achieved by the random copolymer segment A composed of fluoroacrylate / long-chain alkyl acrylate, and the bonding and film-forming properties are mainly achieved by the random copolymer segment B composed of bonding monomer / conventional acrylate monomer.

[0011] Fluoropolymers have low surface energy, and their coatings have excellent "three-repellent" properties. Therefore, the A segment of the block copolymer contains fluoroacrylate monomers, mainly perfluorobutylethyl acrylate, perfluorobutylethyl methacrylate, perfluorohexylethyl acrylate, perfluorohexylethyl methacrylate, perfluorooctylethyl acrylate, perfluorooctylethyl methacrylate, or a mixture thereof. The use of fluoroacrylate monomers is costly. Long-chain alkyl acrylate polymers are crystalline and have certain hydrophobic and oleophobic properties. In particular, when copolymers are formed with fluoroacrylates in a suitable proportion, a "fence" structure can be formed on the surface of the coating to synergistically improve the "three-repellent" properties of the coating. The optional long-chain alkyl acrylate monomers include lauryl acrylate, lauryl methacrylate, hexadecyl acrylate, hexadecyl methacrylate, octadecyl acrylate, octadecyl methacrylate, etc. They can be used alone or in combination. In order to ensure that the coating has excellent "three-repellent" properties, the mass ratio of fluoroacrylate monomers to long-chain alkyl acrylate monomers in the A segment of the block copolymer is 50:50.

[0012] Block copolymers are usually synthesized by living polymerization. Although living ion polymerization was developed early for industrialization, it has the disadvantages of high requirements for the polymerization environment (strictly anhydrous and oxygen-free), the need to use organic solvents, and limited monomer applicability. However, living free radical polymerization has many types, a wide range of applicable monomers, and low requirements for the polymerization environment (such as aqueous phase polymerization), and has become an important way to synthesize block copolymers. In the present invention, the random copolymer segment A is subjected to a chain extension reaction using the bonding component monomer that forms the segment B and the conventional acrylate monomer to form a block copolymer of the segments A and B.

[0013] In order to be suitable for the polymerization of various monomers, avoid the use of organic solvents, improve environmental protection and reduce production costs, the present invention adopts an iodine-compound-regulated (iodine transfer) miniemulsion polymerization one-pot two-step method to directly prepare a block copolymer emulsion that can be coated on a medical protective clothing substrate in one step. The advantage is that not only does it not require impurity removal after the polymerization, but it can also overcome the problem of the difficulty in diffusion of fluorinated monomers in ordinary emulsion polymerization.

[0014] In an embodiment of the present invention, a coating material having high adhesion to fabrics, water-repellent, oil-repellent and blood-repellent is prepared by iodine transfer miniemulsion polymerization using a one-pot two-step method: (1) based on 100 parts of the total amount of raw materials required for the first step reaction, 0.97 parts of the main emulsifier is dissolved in 54.50 parts of deionized water as the aqueous phase; 0.15 parts of iodide chain transfer agent, 1.94 parts of auxiliary emulsifier and 32.25 parts of fluoroacrylate / long-chain alkyl acrylate (16.125 parts each) monomer are mixed to obtain an oil phase; (2) the above aqueous phase and oil phase are fully stirred and mixed and ultrasonically dispersed for 5-10 minutes to obtain a miniemulsion; (3) the obtained miniemulsion is added to a reactor, stirred, argon is passed through and oxygen is discharged for 30 minutes, and then the temperature is raised to 50-60°C. °C, add 10 parts of aqueous solution containing 0.19 parts of initiator to start polymerization, react for 6 to 8 hours and then cool to room temperature; (4) carry out the second step chain extension reaction based on the first step reaction, determine the total mass of monomers added in the second step by the mass ratio range of 30:70 to 70:30 of the monomers added in the first step reaction and the second step reaction, then add 33.27 parts of the bonding component / conventional component mixed monomer and 56.54 parts of deionized water to the emulsion obtained in the first step reaction, stir and swell until the emulsion is not separated, and then heat to 50 to 60 °C, and add 10 parts of aqueous solution containing 0.19 parts of initiator, and polymerize for 3 to 5 hours to obtain the final emulsion product. The emulsion is coated on a fabric substrate and dried to form a coating material.

[0015] The main emulsifier used in the miniemulsion polymerization is one of hexadecyltrimethylammonium bromide and sodium dodecyl sulfate, and the auxiliary emulsifier is one of n-hexadecane, octoxynol and Tween. The polymerization initiator uses a water-soluble initiator, which is one of azobisisobutylamidine hydrochloride, ammonium persulfate and potassium persulfate. The chain transfer agent is one of iodoform, perfluoroiodohexane and perfluoroiodooctane.

[0016] Compared with the coating materials with "three-repellent" properties used in existing medical protective clothing and their preparation methods, the main advantages of the present invention include: the "three-repellent" polymer components and the bonding polymer exist in the form of blocks, and by utilizing microphase separation and the surface enrichment characteristics of fluorine-containing chain segments, the "three-repellent" polymer components and the bonding polymer each perform their respective functions, effectively avoiding the antagonistic effect between different components of the random copolymer and effectively reducing the use of expensive fluorine-containing monomers; iodine transfer miniemulsion polymerization is used to completely avoid the use of organic solvents, chain transfer agents are easily available, and the main / auxiliary emulsifiers are compounded, so the emulsion has high stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A simplified flow chart of the preparation of a coating that has strong adhesion to fabrics and is water, oil and blood repellent. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below.

[0019] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0020] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0021] The embodiments of the present invention are further described below with reference to a plurality of embodiments. Example 1

[0022] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0023] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Example 2

[0024] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0025] The total mass of monomers added in the first step reaction is determined to be 7 / 3 of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed to remove oxygen for 30 minutes, and stirred to fully disperse and swell; the reaction liquid is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 hours, and cooled to obtain the final AB block copolymer emulsion. The base material is cut to a certain size, the AB block copolymer emulsion is coated on the substrate, and the coating material is obtained by drying in an oven, wherein the mass ratio of block A to block B is 30:70. Example 3

[0026] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0027] The total mass of monomers added in the first step reaction is determined to be 3 / 7 of the total mass of monomers added in the first step reaction. Based on 100 parts of the total amount of raw materials added in the second step reaction, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed to remove oxygen for 30 minutes, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 hours, and cooled to obtain the final AB block copolymer emulsion. The base material is cut to a certain size, the AB block copolymer emulsion is coated on the substrate, and the coating material is obtained by drying in an oven, wherein the mass ratio of block A to block B is 70:30. Example 4

[0028] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0029] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 13.308 parts of glycidyl methacrylate and 19.962 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 minutes, and stirred to fully disperse and swell; the reaction solution is heated to 60 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 hours, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Example 5

[0030] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as an auxiliary emulsifier were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 60 ° C, 10 parts of deionized water dissolved with 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0031] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 9.981 parts of glycidyl methacrylate and 23.289 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 minutes, and stirred to fully disperse and swell; the reaction solution is heated to 60 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 hours, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Example 6

[0032] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0033] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of ethyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 minutes, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 hours, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Example 7

[0034] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0035] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of butyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 minutes, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 hours, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Example 8

[0036] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0037] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of acrylic acid and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 50 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 3 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Example 9

[0038] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0039] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of hydroxyethyl acrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 4 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Example 10

[0040] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0041] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl acrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 11

[0042] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0043] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of acryloyl morpholine and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through and oxygen is discharged for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 4 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Example 12

[0044] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl methacrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as an auxiliary emulsifier were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a miniemulsion, and the obtained miniemulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 50°C, 10 parts of deionized water dissolved with 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 7.5 hours, and the block A emulsion was obtained after cooling to room temperature.

[0045] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 13

[0046] Based on 100 parts of the total amount of raw materials added for the first step reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorobutylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 7 hours, and the block A emulsion was obtained after cooling to room temperature.

[0047] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 14

[0048] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorobutylethyl methacrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as an auxiliary emulsifier were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a miniemulsion, and the obtained miniemulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water dissolved with 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 6.5 hours, and the block A emulsion was obtained after cooling to room temperature.

[0049] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 15

[0050] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorooctylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 10 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 60 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0051] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Example 16

[0052] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorooctylethyl methacrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as an auxiliary emulsifier were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 10 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 60 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0053] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 17

[0054] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl methacrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as an auxiliary emulsifier were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water dissolved with 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 7 hours, and the block A emulsion was obtained after cooling to room temperature.

[0055] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 18

[0056] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of lauryl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as an auxiliary emulsifier were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 6 hours, and the block A emulsion was obtained after cooling to room temperature.

[0057] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 19

[0058] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of lauryl methacrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a miniemulsion, and the obtained miniemulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water dissolved with 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 6 hours, and the block A emulsion was obtained after cooling to room temperature.

[0059] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 20

[0060] Based on 100 parts of the total amount of raw materials added for the first step reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of hexadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 7.5 hours, and the block A emulsion was obtained after cooling to room temperature.

[0061] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 21

[0062] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of hexadecyl methacrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as an auxiliary emulsifier were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a miniemulsion, and the obtained miniemulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water dissolved with 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 6.5 hours, and the block A emulsion was obtained after cooling to room temperature.

[0063] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 22

[0064] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of sodium dodecyl sulfate as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of potassium persulfate initiator were added, the reaction was kept warm for 8 h, and the block A emulsion was obtained after cooling to room temperature.

[0065] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of potassium persulfate initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 23

[0066] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of sodium dodecyl sulfate as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of ammonium persulfate initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0067] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of ammonium persulfate initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 24

[0068] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of octoxynol as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55 °C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 h, and the block A emulsion was obtained after cooling to room temperature.

[0069] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 25

[0070] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of Tween as an auxiliary emulsifier were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0071] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 26

[0072] Based on 100 parts of the total amount of raw materials added for the first step reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of iodoform and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55 °C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0073] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3. Embodiment 27

[0074] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodooctane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55 °C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0075] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 16.635 parts of glycidyl methacrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3.

[0076] Comparative Example 28

[0077] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0078] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 8.3175 parts of glycidyl methacrylate, 8.3175 parts of methoxyethyl acrylate and 16.635 parts of methyl acrylate mixed monomers are prepared, mixed with 56.54 parts of deionized water to obtain a water-oil mixture, and the water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed through to remove oxygen for 30 min, and stirred to fully disperse and swell; the reaction solution is heated to 55 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, reacted for 5 h, and cooled to obtain the final AB block copolymer emulsion. Cut the base material of a certain size, apply the AB block copolymer emulsion on the substrate, and put it into an oven to dry to obtain a coating material. Among them, the mass ratio of block A to block B is 66.7:33.3.

[0079] Comparative Example 29

[0080] Based on 100 parts of the total amount of raw materials added in the first step of the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier were dissolved in 54.50 parts of deionized water to form an aqueous phase; 16.125 parts of perfluorohexylethyl acrylate and 16.125 parts of octadecyl acrylate monomers were mixed, and then 0.15 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as auxiliary emulsifiers were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred, and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a fine emulsion, and the obtained fine emulsion was poured into a three-mouth reaction kettle, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55°C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator were added, the reaction was kept warm for 8 hours, and the block A emulsion was obtained after cooling to room temperature.

[0081] The total mass of monomers added in the first step reaction is determined to be half of the total mass of monomers added in the first step reaction. Based on the total amount of raw materials added in the second step reaction of 100 parts, 8.3175 parts of glycidyl methacrylate, 8.3175 parts of N-(3,4-dihydroxyphenylethyl) methacrylamide and 16.635 parts of methyl acrylate mixed monomers are prepared, and mixed with 56.54 parts of deionized water to obtain a water-oil mixture. The water-oil mixture is added to the reactor containing the block A emulsion after the above reaction, sealed to avoid light, argon is passed to remove oxygen for 30 minutes, and stirred to fully disperse and swell; the reaction liquid is heated to 50 ° C, 10 parts of deionized water containing 0.19 parts of azobisisobutylamidine hydrochloride initiator are added, the reaction is carried out for 5 hours, and the final AB block copolymer emulsion is obtained by cooling. The substrate material is cut to a certain size, the AB block copolymer emulsion is coated on the substrate, and the coating material is obtained by drying in an oven. The mass ratio of block A to block B is 66.7:33.3.

[0082] Comparative Example 30

[0083] The random copolymer was synthesized by iodine transfer miniemulsion polymerization as a comparative example. Based on 100 parts of the total amount of raw materials required for the reaction, 0.97 parts of hexadecyltrimethylammonium bromide as a primary emulsifier was dissolved in 42.97 parts of deionized water to form an aqueous phase; 10.74 parts of perfluorohexylethyl acrylate, 10.74 parts of octadecyl acrylate, 2.69 parts of glycidyl methacrylate, 2.69 parts of glycidyl methacrylate N-(3,4-dihydroxyphenylethyl) methacrylamide and 5.38 parts of methyl acrylate were mixed, and then 0.11 parts of perfluoroiodohexane and 1.94 parts of n-hexadecane as an auxiliary emulsifier were added to form an oil phase; the aqueous phase and the oil phase were fully mixed, stirred and ultrasonicated for 5 min using an ultrasonic cell crusher to obtain a miniemulsion, and the obtained miniemulsion was poured into a three-mouth reactor, magnetic stirring was maintained, the device was sealed to avoid light, and argon was passed to exhaust oxygen; the reaction solution was heated to 55 °C, add 21.50 parts of deionized water dissolved with 0.27 parts of azobisisobutylamidine hydrochloride initiator, keep warm for 12 hours, and cool to room temperature to obtain a random copolymer emulsion containing AB components. Among them, the mass ratio of component A to component B is still controlled at 66.7:33.3.

[0084] The design strategy, advantages, processes, and performance of the present invention will be further described below.

[0085] The design strategy of the present invention is to design block copolymers to respectively play the "liquid repelling" function and the bonding function, and compare with the current mainstream random copolymer coating: from the perspective of surface molecular arrangement, when the raw materials are the same, the components of the random copolymer are disorderly arranged on the substrate surface, the functional components are mixed with the conventional components, and the function realization efficiency is low. Block copolymers can effectively overcome this defect. The microphase separation property of block copolymers makes it highly controllable, and the molecular arrangement of block copolymers at the interface can be regulated by many means. Taking this invention as an example, the "liquid repelling" component is designed in block A, and the bonding component and the conventional component are designed in block B. Under certain conditions, block A will be enriched at the air interface due to the low surface energy, while the bonding component and the conventional component are firmly adhered to the substrate surface, thus forming a topological structure of a polymer brush, which is conducive to each component performing its duties and efficiently playing its own role. Based on this, the design of block copolymers can ensure that the adhesion component adopts some monomers with strong polarity, and further enhances the adhesion to the substrate without losing the requirement of "three rejections" of the coating. Under the same target performance, the block copolymer will be used in less amount than the random copolymer, and the cost will be lower. Comparing Examples 29 and 30, under the same raw material formula, the design of the block copolymer can obtain a coating with better "three-rejection" effect, while the random copolymer will cause the presence of polar components on the surface due to the random arrangement of the surface, thereby greatly affecting the surface hydrophobic and oleophobic properties.

[0086] Attached Figure 1 A brief preparation process of a "liquid repellent" coating that demonstrates adhesion function, first the synthesis of the polymer, the process of which has been described in detail in the specific implementation, and then the obtained miniemulsion is coated on the desired substrate in one step. This process avoids the use of organic solvents, and the miniemulsion has good dispersion, avoiding uneven agglomeration of the polymer. After the coating is completed, it is sent to the oven for drying to obtain the finished product, which is simple and environmentally friendly.

[0087] Table 1 lists the molecular weight and distribution of the synthesized block copolymers. Table 2 lists the surface static water-oil contact angle and adhesion performance to polyethylene terephthalate substrate. The results show that the polymer coating surface designed by the invention has relatively good "liquid repellency". Adhesion performance is divided into 6 levels from 0B to 5B from poor to good according to ANSI / ASTM D3359-17 standard. The results show that the adhesion effect of the coatings in different embodiments is good.

[0088] Table 1 lists the molecular weight and distribution of the block copolymers of Examples 1 to 30

[0089]

[0090] Table 2 lists the static contact angles of water and n-hexadecane and the adhesion properties of the coating surfaces of Examples 1 to 30.

[0091]

[0092] Although some specific embodiments of the present invention are described in detail above, various modifications and changes can be made to these embodiments for professionals in the field. For example, in terms of block copolymer monomer selection, "three rejection" monomers and long-chain alkyl monomers can be selected in any combination, and can be arbitrarily matched according to a mass ratio of 50:50. Adhesive monomers and conventional monomers can also be selected in any combination, and can be arbitrarily matched according to a mass ratio of 30:70~50:50. Block A and block B monomers can be arbitrarily combined and matched in a mass ratio of 30:70~70:30. In terms of synthesis conditions, the choice of reaction temperature is closely related to the use temperature of the chain transfer agent and the half-life of the initiator. To ensure that the chain transfer agent is not inactivated, the initiator is selected when the decomposition time at the reaction temperature is reasonable. In addition, while ensuring the conversion rate, the reaction time and reaction temperature must also be matched to ensure a good polymerization process. It should be understood that such modifications and changes are within the scope and spirit of the present invention described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A fabric coating material, characterized in that: The invention is a block copolymer comprising a random copolymer segment A of fluoroacrylate / long-chain alkyl acrylate and a random copolymer segment B of adhesive monomer / conventional acrylate monomer; the mass ratio of segment A to segment B is 66.7:33.3-70:30; and the adhesive component monomer of segment B is one of glycidyl acrylate, glycidyl methacrylate, methoxyethyl acrylate and N-(3,4-dihydroxyphenylethyl) methacrylamide monomers; the conventional acrylate monomer is one of methyl acrylate, ethyl acrylate and butyl acrylate monomers or a mixture thereof; the mass ratio of the adhesive component monomer to the conventional acrylate monomer is 13.308:19.962-50:50; The fluoroacrylate monomer in segment A is one of perfluorobutyl ethyl acrylate, perfluorohexyl ethyl acrylate, perfluorooctyl ethyl acrylate, and perfluorooctyl ethyl methacrylate; the long-chain alkyl acrylate monomer is one of lauryl acrylate, lauryl methacrylate, hexadecyl acrylate, hexadecyl methacrylate, octadecyl acrylate, and octadecyl methacrylate monomers, or a mixture thereof.

2. The fabric coating material according to claim 1, characterized in that: The mass ratio of the fluoroacrylate monomer to the long-chain alkyl acrylate monomer in segment A is 50:

50.

3. The method for preparing a fabric coating material according to claim 1, characterized in that: At least: (1) Synthesizing random copolymer segment A; (2) Adding a bonding component monomer for forming segment B and a conventional acrylate monomer to carry out a chain extension reaction to form a block copolymer of segment A and segment B, wherein the mass ratio of segment A to segment B is 66.7:33.3~70:

30.

4. The method for preparing a fabric coating material according to claim 3, characterized in that: In step 2, the bonding component monomer, conventional acrylate monomer and deionized water are added to the emulsion of the random copolymer segment A, stirred, dispersed and swelled, heated to 50-60° C., and 10 parts of an aqueous solution containing 0.19 parts of an initiator are added, and the final emulsion product is obtained after polymerization for 3-5 hours.

5. The method for preparing a fabric coating material according to claim 3, characterized in that: The random copolymer segment A was synthesized by the following scheme: Dissolve 0.97 parts of primary emulsifier in 54.50 parts of deionized water as the aqueous phase; Mix 0.15 parts of an iodide chain transfer agent, 1.94 parts of a co-emulsifier, 16.125 parts of a fluoroacrylate monomer, and 16.125 parts of a long-chain alkyl acrylate monomer to obtain an oil phase; The above aqueous phase and oil phase were stirred and mixed and ultrasonically dispersed for 5-10 min to obtain a miniemulsion; The obtained miniemulsion was added into the reactor, stirred and purged with argon for 30 min, then the temperature was raised to 50-60°C, 10 parts of an aqueous solution containing 0.19 parts of an initiator was added to start polymerization, and the reaction was continued for 6-8 h before cooling to room temperature.

6. The method for preparing a fabric coating material according to claim 5, characterized in that: The main emulsifier is one of hexadecyltrimethylammonium bromide and sodium lauryl sulfate.

7. The method for preparing a fabric coating material according to claim 5, characterized in that: The auxiliary emulsifier is one of n-hexadecane, octoxynol and Tween.

8. The method for preparing a fabric coating material according to claim 5, characterized in that: The initiator is one of azobisisobutylamidine hydrochloride, ammonium persulfate and potassium persulfate.

9. The method for preparing a fabric coating material according to claim 5, characterized in that: The chain transfer agent is one of iodoform, perfluoroiodohexane and perfluoroiodooctane.

Citation Information

Patent Citations

  • Super-hydrophobic and super-oleophobic modified liquid and preparation method thereof, and coating containing super-hydrophobic and super-oleophobic modified liquid

    CN116355444A

  • Nano coating with high wear resistance, high weather resistance, super-hydrophobicity and super-oleophobicity as well as preparation method and construction method of nano coating

    CN116622288A

  • Transparent hydrophobic and oleophobic coating, preparation method thereof and formed transparent hydrophobic and oleophobic coating

    CN116694115A

  • Fluorine-containing block copolymer and application thereof

    CN103788316A